Improving Competitive Advantage from Costumer Perspective: Strategic Approaches in Indonesia’s Telecom Sector - Bo, Liu; Damayanti, Sylviana Maya; Jagat Prirayani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study examines Smartfren’s market position, competitive advantage, and growth prospects amid Telkomsel’s market dominance. It employs primary survey data from users and professionals and secondary industry reports, analyzed through a quantitative approach and Porter’s Five Forces framework. The findings reveal Telkomsel’s superiority in market share, network coverage, and technological innovation, while Smartfren offers stronger value in pricing and economic appeal. High industry rivalry, strong buyer power, and rising digital substitutes push both providers to innovate continuously. The study offers strategic insights for telecom firms and policymakers, and recommends broader sampling, inclusion of more operators, longitudinal analysis, and further research on consumer behavior and digital ecosystems.